THE PYROCARBON FORMATION MECHANISM DURING THE HYDROCARBON PYROLYSIS PROCESS - B. V. Peshnev; A. S. Filimonov; S. V. Baulin; O. S. Sledz; N. Yu. Asilova (Тонкие химические технологии, 2017)
Experimental results confirming the mechanism of pyrocarbon formation through the steps of high-molecular pyrolysis products forming in the gas phase are presented. Adsorption of high-molecular pyrolysis products on the active centers of the substrate localized at the boundaries of the contacts of its crystallites and their subsequent carbonization is confirmed. The decreasing in the length of the substrate crystallites contact boundaries leads to the increase in the content of high-molecular compounds in the gas and to the decrease in the hydrogen concentration is shown. The relation between the composition of the exhaust gas and the surface of the sealing material creates the prerequisites for controlling the pyro-consolidation process according the composition of the off-gas. The composition of high-molecular liquid pyrolysis products was identified. The difference in the composition of high-molecular pyrolysis products of the propane-butane fraction and the electric cracking gas was established. The influence of raw materials and pyrolysis conditions on the group composition of high-molecular pyrolysis products formed is shown.